Effects of doxepin on isolated basilar and saphenous artery rings of rabbits - Qi Min; Hu Xiang-Jie; LÜ Ai-Gang; Ke Jun; Zhang Gui-Qing (Acta Pharmacologica Sinica, 2016)
AIM: To study the effects of doxepin (Dox) on cerebral artery. METHODS: The effects of Dox were observed using the isolated basilar and saphenous artery rings of rabbits. RESULTS: Dox inhibited the constriction of the basilar and saphenous artery rings evoked by KCl with IC50 5.75 mumol.L-1 (95% confidence limits were 2.3-14 mumol.L-1, n = 8) and 34.6 mumol.L-1 (95% confidence limits were 3.8-316 mumol.L-1, n = 8), respectively. Dox also inhibited the constriction of the basilar and saphenous artery rings of the rabbits stimulated by 5-hydroxytryptamine (5-HT), IC50 were 6.3 mumol.L-1 (95% confidence limits were 1.7-23.3 mumol.L-1, n = 7) and 8.0 mumol.L-1 (95% confidence limits were 6.3-10.3 mumol.L-1, n = 6), respectively. In both samples (basilar and saphenous artery rings) CaCl2 evoked, the pD2 of Dox was 5.28 +/- 0.40 and 4.76 +/- 0.14, respectively (n = 6, P < 0.01). Dox 5.8 mumol.L-1 inhibited the constriction of the saphenous artery evoked by norepinephrine (NE) in Ca(2+)-free medium. Dox 30 mumol.L-1 inhibited the constriction of the saphenous artery evoked both by NE and by readmission of CaCl2 (1.25 mmol.L-1). CONCLUSION: As compared with its effect on the saphenous artery, Dox selectively inhibited the basilar artery.